2017
DOI: 10.1021/acssuschemeng.7b00194
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Concrete Water Reducer via Fractionation and Modification of Lignin Extracted from Pine Wood by Formic Acid

Abstract: In this work, a lignin-based concrete water reducer was prepared through organic solvent fractionation and chemical modification of lignin extracted from pine wood with formic acid. The fractionated lignin with different molecular weight was modified via oxidation–sulfomethylation (OS), and the effects of fractionation on the performance of lignin-based concrete water reducer were investigated. It was found that the sulfonation degree (SD) of the fractionated lignin after OS was clearly higher compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…The hybrid materials used in the tests as admixtures for the mortar resulted in a final increase of the slump result (23.5–25.0 cm, depending on the quantities of mortar and biopolymer used). The results show clearly that the addition of biopolymers or of hybrid systems containing biopolymers makes it possible to increase the final slump result of cement mortar, indicating that they act as plasticizers, as has also been confirmed by other authors [15,16,17,18].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The hybrid materials used in the tests as admixtures for the mortar resulted in a final increase of the slump result (23.5–25.0 cm, depending on the quantities of mortar and biopolymer used). The results show clearly that the addition of biopolymers or of hybrid systems containing biopolymers makes it possible to increase the final slump result of cement mortar, indicating that they act as plasticizers, as has also been confirmed by other authors [15,16,17,18].…”
Section: Resultssupporting
confidence: 82%
“…Those authors conducted a series of experiments on an aluminum plate, and the results clearly indicated the high potential of coatings with a high lignin content as anti-corrosive agents. There are also several literature reports that describe the direct use of lignin as an agent reducing the amount of mixing water for the production of cement mixtures [15,16] or as a plasticizing agent [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in these characteristics due to different lignin origins and processing/extraction methods can cause significant alterations in the performance of the final product [24]. A critical dependence on lignin properties was found for several high-value applications [25][26][27][28], such as the production of polymers [16], antioxidants [29], aromatic compounds [30], the synthesis of vanillin [31], and the development of high-performance concrete water-reducing agents [32]. The availability of effective fractionation processes for obtaining lignins with tailored physico-chemical properties and a defined molecular weight distribution is therefore a key requirement to effectively cope with both the upstream material variability and the downstream application requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of publications [40][41][42][43] also observed an increase in the plasticity of mixtures with the addition of lignin or its derivatives. Kalliola et al [40] reported a beneficial effect of the admixture of oxidized lignin on the flow rate for pastes, mortars and concretes.…”
Section: Slump Test Resultsmentioning
confidence: 94%
“…Moreover, in their tests, it was confirmed that this admixture had no negative impact on the compressive strength of the mature concrete and the aeration of the mix. In their study, Li et al [41] obtained lignin from pinewood, and then subjected it to a series of solvent modifications to obtain a lignin-based water reducer. The authors showed the influence of the sulfonation degree of the obtained lignin on the workability of pastes, including their plasticity.…”
Section: Slump Test Resultsmentioning
confidence: 99%